Barriers to the Adoption of Digital Health Solutions Among Type 2 Diabetic Patients During the COVID-19 Pandemic - Thanthrige, Ayesha; Dang, Thu Ha; Wickramasinghe, Nilmini (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
The world faces unexpected disruptions, such as the COVID-19 pandemic. These situations expose gaps, specifically in healthcare, and highlight the need for digital health solutions (DHSs). However, managing chronic conditions like Type 2 Diabetes Mellitus (T2DM) becomes challenging during such crises, especially in the U.S. where T2DM is highly prevalent. These challenges offer lessons for better preparedness. Prior studies have overlooked the specific barriers to DHS adoption among T2DM patients. This study addresses this gap by investigating adoption barriers for U.S. T2DM patients. Using the Unified Theory of Acceptance and Use of Technology (UTAUT) and a PRISMA-guided systematic review, we identified key barriers such as infrastructure limitations, usability issues, socio-economic disparities, privacy concerns, and perceived usefulness limitations. Findings recommend enhancing digital infrastructure, simplifying interfaces, and strengthening security measures to improve adoption and long-term use. These insights guide DHS implementation for T2DM, with broader implications for chronic disease management globally, addressing healthcare disruptions beyond COVID-19.